2017
DOI: 10.1002/acr.23006
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of Patient‐Reported Joint Symptoms, Physician‐Examined Arthritic Signs, and Ultrasound‐Detected Synovitis in Rheumatoid Arthritis

Abstract: Joint swelling showed the best concordance with ultrasonography, followed by patient-reported joint symptoms, and joint tenderness. Joint symptoms, rather than tenderness evaluation, may be a better clinical indicator of synovitis in RA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 31 publications
0
14
1
1
Order By: Relevance
“…A cross-sectional study of 50 patients with RA found patient-reported symptoms (pain and joint stiffness) to have higher concordance with ultrasound findings than joint tenderness 40. In the present study, PRJP and tender joints were highly correlated at patient level but with only fair concordance at joint level, and both had low associations with swollen joints and ultrasound scores at patient as well as joint level.…”
Section: Discussioncontrasting
confidence: 45%
“…A cross-sectional study of 50 patients with RA found patient-reported symptoms (pain and joint stiffness) to have higher concordance with ultrasound findings than joint tenderness 40. In the present study, PRJP and tender joints were highly correlated at patient level but with only fair concordance at joint level, and both had low associations with swollen joints and ultrasound scores at patient as well as joint level.…”
Section: Discussioncontrasting
confidence: 45%
“…This kind of problem can also be seen in the study of Hirata et al , also published in Arthritis Care & Research . The purpose of that article was not to evaluate the use of MTX, but to check the concordance between patient‐reported joint symptoms, physician‐examined arthritic signs, and ultrasound‐detected synovitis in RA.…”
mentioning
confidence: 63%
“…These factors may contribute to overcalling synovitis by clinical examination/patient-report. Furthermore, it has been observed that the degree and direction of discrepancy between clinically and ultrasonography-detected synovitis may be related to joint region and size: superior concordance has been observed for larger joints (shoulder, elbow, knee and ankle) compared to smaller joints (PIP, MCP and wrist) (38).…”
Section: Discussionmentioning
confidence: 99%
“…To date, only few studies assessed the relationship between patients' self-assessment of joints and ultrasonography signs of inflammation (18,(37)(38)42). Direct comparisons across studies are challenging because different ultrasonography scoring systems are used in different sets of joints/ sites, and different measures of agreement are used.…”
Section: Discussionmentioning
confidence: 99%